The Role of Financial Technology in Enhancing Investment Decisions and Risk Management for SMEs - Herdiyana; Yan Noviar Nasution (Jurnal Ilmiah Manajemen Kesatuan, 2025)
In the evolving financial landscape, Small and Medium Enterprises (SMEs) face persistent challenges in making informed investment decisions and managing risks due to limited access to financial data, expertise, and infrastructure. Financial Technology (FinTech) has emerged as a transformative solution, offering innovative platforms and tools that democratize access to financial services, improve transparency, and enhance data-driven decision-making. This study aims to explore the role of FinTech in supporting investment decision-making and risk management among SMEs through a comprehensive literature review approach. The methodology involves a systematic analysis of peer-reviewed articles, industry reports, and academic studies published between 2015 and 2024. Key themes analyzed include algorithmic investment platforms, digital credit scoring, real-time financial analytics, blockchain-based transparency, and automated risk monitoring tools. The findings indicate that FinTech facilitates improved investment decisions through enhanced financial forecasting, scenario simulations, and access to alternative financing channels. In terms of risk management, FinTech enables SMEs to identify potential financial threats early, leverage predictive analytics, and maintain regulatory compliance more efficiently. The study contributes to the growing discourse on digital financial inclusion and highlights FinTech’s potential as a strategic enabler for SME sustainability and competitiveness in uncertain economic environments. It also underscores the need for policy frameworks that support digital adoption and safeguard against technology-related risks. Overall, the integration of FinTech into SME operations marks a paradigm shift toward more resilient, data-driven financial practices.